The Effectiveness of use of Artificial Intellegence (AI) in Supporting the Learning of Students Department of Educational Technology State University of Malang - Kaulika, Vania Wilona; Praherdhiono, Henry; Utami, Deka Dyah (Proceedings Series of Educational Studies, 2024)
Nowadays use Artificial Intelligence (AI) has received controversy in various fields, but this research wants to explore the potential of AI in supporting learning. One of the most widely used AI products is Chat GPT (Generative Pre-trained). The purpose of this research is to describe the usefulness, convenience, behavioral intentions, and actual use of GPT Chat in learning for students at the Faculty of Education, State University of Malang using the model. Technology Acceptance Model (TAM). TAM is a theoretical approach to describe the level of acceptance of technology. This research uses a quantitative descriptive approach and data processing uses statistics. The results of this research found that the use of GPT Chat by generation Z State University of Malang students proved effective in supporting their learning. So it was concluded that the average of the 4 variables of usefulness, convenience, behavioral intention and actual use of Chat GPT in supporting the learning of Educational Technology students at the State University of Malang was included in the good/high category with an average score (Mean) of 57.00 and a percentage of 71.25%. Keywords : Chat GPT, TAM, Learning